Technical issues in test process assessment and their current handling in TestSPICE. Issue 3 (26th February 2013) - Schweigert, Tomas; Nehfort, Andreas; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
<x xml:space="preserve">Abstract</x> Looking at normal test activities such as test preparation or test execution, setting up a Process Reference Model or a Process Assessment Model seems to be quite easy, but when discussion focuses on technical issues, it becomes really challenging. This paper describes the current handling of those issues in the TestSPICE approach and also some potential pitfalls. Copyright © 2013 John Wiley & Sons, Ltd.